Transparency Isn't Spoon-Feeding: How a Transformative Approach to the Use of Explicit Assessment Criteria Can Support Student Self-Regulation - Balloo, Kieran; Evans, Carol; Hughes, Annie; Zhu, Xiaotong; Winstone, Naomi (Frontiers in Education, 2018)
If little care is taken when establishing clear assessment requirements, there is the potential for spoon-feeding. However, in this conceptual article we argue that transparency in assessment is essential to providing equality of opportunity and promoting students’ self-regulatory capacity. We begin by showing how a research-informed inclusive pedagogy, the EAT Framework, can be used to improve assessment practices to ensure that the purposes, processes, and requirements of assessment are clear and explicit to students. The EAT Framework foregrounds how students’ and teachers’ conceptions of learning (i.e., whether one has a transactional or transformative conception of learning within a specific context) impact assessment practices. In this article, we highlight the importance of being explicit in promoting access to learning, and in referencing the EAT Framework, the importance of developing transformative rather than transactional approaches to being explicit. Firstly, we discuss how transparency in the assessment process could lead to ‘criteria compliance’ and learner instrumentalism if a transactional approach to transparency, involving high external regulation, is used. Importantly, we highlight how explicit assessment criteria can hinder learner autonomy if paired with an overreliance on criteria-focused ‘coaching’ from teachers. We then address how ‘being explicit with assessment’ does not constitute spoon-feeding when used to promote understanding of assessment practices, and the application of deeper approaches to learning as an integral component of an inclusive learning environment. We then provide evidence on how explicit assessment criteria allow students to self-assess and self-regulate, noting that explicit criteria may be more effective when drawing on a transformative approach to transparency, which acknowledges the importance of transparent and mutual student-teacher communications about assessment requirements. We conclude by providing recommendations to teachers and students about how explicit assessment criteria can be used to improve students’ learning. Through an emphasis on transparency of process, clarity of roles, and explication of what constitutes quality within a specific discipline, underpinned by a transformative approach, students and teachers should be better equipped to self-manage their own learning and teaching.